Higher levels of person-centred care are associated with lower levels of stress of conscience in hospital and municipal care: cross-sectional findings from the PCC@Work project - Kristoffer Gustavsson; Andreas Fors; Cornelia van Diepen; Malin Axelsson; Monica Bertilsson; Angela Bångsbo; Gunnel Hensing; Qarin Lood (BMC Health Services Research)
Abstract Background Stress of conscience is common in health and social care, being associated with adverse health consequences, staff turnover, and poor care quality. Person-centred care (PCC), an ethical approach to care with potential to reduce stress of conscience, has been little explored across healthcare settings. This study assesses the association between perceived PCC and stress of conscience among health and social care professionals in hospital and municipal care settings. Methods A web survey was sent to 11,554 health and social care professionals employed in hospital and municipal care settings in western Sweden. It yielded 2123 responses, and cross-sectional analyses were performed with data from 1671 professionals. The Person-Centred Care Assessment Tool was used to measure PCC, for both the full scale (P-CAT) and its subscales “Extent of Personalising Care” (EPC) and “Organisational and Environmental Support” (OES). The Stress of Conscience Questionnaire (SCQ) was used to measure the outcome stress of conscience. Bivariate correlations and linear regressions were used to analyse the data. Results The bivariate correlations were significant and negative for P-CAT (r s = − 0.399, p < 0.01), EPC (r s = − 0.239, p < 0.01), and OES (r s = − 0.482, p < 0.01) with SCQ. When adjusted for covariates, multivariate linear regressions identified negative associations for P-CAT (B = − 1.16, 95% CI − 1.33, − 0.99, p < 0.001), EPC (B = − 0.8, 95% CI − 1.04, − 0.56, p < 0.001), and OES (B = − 3.14, 95% CI − 3.52, − 2.78, p < 0.001) with SCQ, indicating that as the scores of P-CAT and its subscales increase, the SCQ score decreases. Conclusions Our findings revealed that hospital and municipal health and social care professionals who perceived higher levels of PCC also perceived lower levels of stress of conscience. Considering the increased focus on PCC internationally, the results are relevant, as PCC might be one possible approach to mitigate stress of conscience. More knowledge of EPC and OES in relation to stress of conscience could be important for improved and better-targeted PCC implementation efforts.